An additive-free silicon anode in nanotube morphology as a model lithium ion battery material - Zhuo, Ying; Sun, Hong; Uddin, Md. Helal; Barr, Maissa; Wisser, Dorothea; Roßmann, Philip Kazys; Esper, Julian Duane; Tymek, Sarah; Döhler, Dirk; Peukert, Wolfgang; Hartmann, Martin; Bachmann, Julien (Electrochimica Acta, 2021)
Ordered arrays of parallel, cylindrical silicon nanotubes are obtained by aluminothermic reduction of SiO2 nanotubes generated by atomic layer deposition (ALD) on nanoporous aluminum oxide templates. The reduction to amorphous Si (a-Si) is characterized by a combination of X-ray diffraction (XRD), solid-state cross-polarization magic-angle spinning nuclear magnetic resonance (29Si CP-MAS NMR), ultraviolet-visible spectroscopy, attenuated total reflectance infrared spectroscopy (ATR-IR), and X-ray photoelectron spectroscopy (XPS). These a-Si nanotube arrays are electrochemically active in a lithium-ion battery environment when prepared on Cu current collectors without any additives. The absence of the traditional additive carbon black, which is an electrochemically inert conductor, increases the proportion of capacity associated with faradaic reactions (Li incorporation) with respect to the capacitive component. Electrochemical impedance spectroscopy (EIS) and charge-discharge tests demonstrate that the nanotube morphology yields an improved tolerance to fast cycling.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Aluminothermic reduction; Anode material; Atomic layer deposition; Lithium ion battery; Si nanotube

Bioactive Glass Flakes as Innovative Fillers in Chitosan Membranes for Guided Bone Regeneration - Zhang, Huijun; Wu, Jingjing; Wan, Ying; Romeis, Stefan; Esper, Julian Duane; Peukert, Wolfgang; Zheng, Kai; Boccaccini, Aldo R. (Advanced Engineering Materials, 2021)
Herein, novel bioactive glass flakes (BGFs) (45S5 composition), obtained by compression in the liquid phase in a stirred media mill, are combined with chitosan (CS) to develop composite membranes using solvent casting for guided bone regeneration (GBR). The incorporation of BGFs endows CS membranes with superior bioactivity as evidenced by rapid hydroxyapatite formation after 3 days of immersion in simulated body fluid (SBF). Moreover, the addition of BGFs reduces the swelling ratio of CS membranes, beneficial for GBR applications. The swelling behavior can also be modulated by tuning the added amount of BGFs. In vitro cell studies indicate the noncytotoxicity of composite membranes toward osteoblast cell line MC3T3-E1, although the presence of BGFs slightly reduces the cell viability compared to pure CS membranes. The incorporation of BGFs also improves the osteogenic differentiation of MC3T3-E1 cells as indicated by the enhanced alkaline phosphatase activity. The results show the feasibility of BGFs as anisotropic bioactive fillers in polymeric matrices. In conclusion, the developed CS-BGF composite membranes show promising potential as a novel material for GBR.
CRIS-Team Scopus Importer:2021-10-08
Keywords: bioactive fillers; bioactive glass flakes; chitosan; composites; guided bone regeneration

Control of Crystallization of PBT-PC Blends by Anisotropic SiO2 and GeO2 Glass Flakes - Düsenberg, Björn; Esper, Julian Duane; Maussner, Felix; Mayerhofer, Magdalena; Schmidt, Jochen; Peukert, Wolfgang; Bück, Andreas (Polymers, 2022)
Polymer composites and blend systems are of increasing importance, due to the combination of unique and different material properties. Blending polybutylene terephthalate (PBT) with polycarbonate (PC) has been the focus of attention for some time in order to combine thermo-chemical with mechanical resistance. The right compounding of the two polymers is a particular challenge, since phase boundaries between PBT and PC lead to coalescence during melting, and thus to unwanted segregation within the composite material. Amorphization of the semi-crystalline PBT would significantly improve the blending of the two polymers, which is why specific miscibility aids are needed for this purpose. Recent research has focused on the functionalization of polymers with shape-anisotropic glass particles. The advantage of those results from their two-dimensional shape, which not only improves the mechanical properties but are also suspected to act as miscibility aids, as they could catalyze transesterification or act as crystallization modifier. This work presents a process route for the production of PBT-PC blends via co-comminution and an in-situ additivation of the polymer blend particles with anisotropic glass flakes to adjust the crystallinity and therefore enhance the miscibility of the polymers.
CRIS-Team Scopus Importer:2022-11-25
Keywords: anisotropic particles; co-comminution; crystallization modifiers; functional filler; glass flakes; polymer-blends

Electrophoretic Deposition of Out‐of‐Plane Oriented Active Material for Lithium‐Ion Batteries - Esper, Julian Duane; Helmer, Alexandra; Wu, Yanlin; Bachmann, Julien; Klupp Taylor, Robin (Energy Technology, 2021)
The performance of secondary batteries, of which the lithium‐ion battery is one of the most well known, depends not only on the active electrode materials but also on the electrode architecture. In particular, the reduction in electrode tortuosity is expected to enable batteries with high active material utilization and fast charging and discharging capabilities. Herein, it is shown how electrophoretic deposition can be used to produce electrodes comprising hybrid particles of cobalt(II,III) oxide‐coated rutile‐mica oriented in an out‐of‐plane fashion. Key to this process is a sacrificial anode which leads to charging of the flake‐shaped particles and formation of a holding layer cementing them perpendicular to the substrate. Moreover, the electrochemical performance of lithium‐ion battery anodes with out‐of‐plane and in‐plane oriented architectures is compared. The out‐of‐plane orientation of the flake‐like particles results in better utilization of active material, lower charge‐transfer impedance, and faster ion diffusion. Moreover, for a range of charge/discharge rates, the specific capacity is over three times higher in comparison to an electrode with the same material oriented in an in‐plane architecture. The approach to electrode structuring is both facile and scalable and can be readily applied in the future to produce other electrochemical energy storage device electrodes.<br
Keywords: electrode architectures; electrophoretic deposition; flake-like hybrid particles; lithium-ion batteries; mica

Phase structure, rheology and electrical conductivity of co-continuous polystyrene/polymethylmethacrylate blends filled with carbon black - Esper, Julian Duane; Scherzer, Selina; Stary, Zdenek; Pavlova, Ewa (Composites Science and Technology, 2015)
In this work the effect of carbon black concentration on the rheology, electrical conductivity and morphology development of PS/PMMA co-continuous blends during quiescent annealing is investigated. In the blends studied carbon black is preferentially localized in the PS. The specific interfacial length, which is taken as a measure of fineness of blends morphology, increases linearly with the carbon black content in the blends after melt mixing. However, significant suppression of the structure coarsening during annealing is observed in systems with more than 3 vol.% of carbon black, in which the filler structures induce pronounced flow restrictions. The final change in the flow behaviour of the blend induced by annealing is a result of competition between morphology coarsening and particle structure formation and it depends on the concentration of carbon blac
Keywords: Annealing; Polymer-matrix composites; Electrical properties; Scanning electron microscopy; Rheology

Preparation, formulation and deposition of mica flake supported cobalt oxide for nanostructured lithium ion battery anodes - Helmer, Alexandra; Rink, Anna; Esper, Julian Duane; Wu, Yanlin; Bachmann, Julien; Klupp Taylor, Robin (Advanced Powder Technology, 2019)
Abstract We describe the fabrication and morphological and electrochemical characterisation of lithium ion battery anodes whereby the active material is supported on flake-like microparticles. Using various physical analytical techniques we verify that nanostructured cobalt (II, III) oxide can be directly grown onto commercial titanium dioxide-coated mica flakes by a liquid phase oxidation route. We then investigate the formulation and deposition of this material along with carbon black in order to form electrodes. Here we consider two binder/solvent systems, one widely used based on polyvinylidene fluoride in N-methy-2-pyrrolidone, and one more recently identified based on sodium alginate in water. We show that the latter system is preferable for the formation of anodes using the cobalt oxide coated flake-like particles as it leads to a more homogeneous distribution of active and conductive material in the electrode. Using cyclic voltammetry and electrochemical impedance spectroscopy we show that this feature improves the access to active material and facilitates efficient charge transfer in the electrode while maintaining electrode integrity. Moreover, an electrode based on the alginate binder exhibited a high reversible specific capacity of 650 mAh/g along with 84.8% capacity retention after 70 cycles. Overall our study indicates the promise of including shape anisotropic particles such as microflakes in battery electrodes.<br
Keywords: Particle coating; Formulation; Deposition; Battery electrode; Electrochemistry

Scalable production of glass flakes via compression in the liquid phase - Esper, Julian Duane; Liu, Lingfeng; Willnauer, Johannes; Strobel, Alexander; Schwenger, Jan; Romeis, Stefan; Peukert, Wolfgang (Advanced Powder Technology, 2020)
A comprehensive study on controlled shape formation with high yield of three commercially relevant SiO2-based amorphous glasses in a stirred media mill is presented. Stressing under well-controlled conditions leads to micron-sized amorphous glass flakes with high aspect ratios. This unique result is quite contrary to the fundamental observation that comminution processes generally result in irregular shaped particles. The influences of glass composition, processing time, stirrer tip speed and grinding media size on the obtained products have been investigated. The size and shape of the obtained glass flakes have been characterized by scanning electron microscopy and atomic force microscopy. The glass flakes exhibit thicknesses as low as 155 nm while the lateral dimensions are well within the micrometer range. Our study shows that particle size reduction occurs within the first hour of grinding. Afterwards plastic deformation of the fragments, which can be accompanied by densification of the glass network, leads to the formation and further thinning of the glass flakes. To demonstrate the quality and applicability of the glass flakes interference pigments were realized by a TiO2 coating via an aqueous titration process. The presented approach offers a simple, convenient and fully scalable top-down method to produce flake-like particles from various silica glasses. The obtained flakes are suitable substrates for further modifications and applications and the process can be transferred to other materials and glasses with tailor-made chemical composition
Keywords: Stirred media mill; Comminution; Liquid phase compression; Particle processing; Glass flakes; Pigments

Shape-anisotropic cobalt-germanium-borate glass flakes as novel Li-ion battery anodes - Esper, Julian Duane; Zhuo, Ying; Barr, Maissa; Yokosawa, Tadahiro; Spiecker, Erdmann; de Ligny, Dominique; Bachmann, Julien; Peukert, Wolfgang; Romeis, Stefan (Powder Technology, 2020)
Novel CoO-Li2O-B2O3 and CoO-GeO2-Li2O-B2O3 flake-like glass particles for battery applications are produced by an innovative technique: Glasses from melt quenching are processed into micron-sized glass flakes in a stirred media mill. Processing under well-controlled conditions yields flake-like particles with high aspect ratios which are suitable for anodes in Lithium-ion batteries. Electrochemical characterization by cyclic voltammetry, electrochemical impedance spectroscopy, galvanostatic charge/discharge cycles and rate capability measurements indicates that the flakes show superior electrochemical properties compared to the bulk glass counterparts with a stable specific capacity of 620 mAh g−1 after 100 cycles. The majority of charge is stored by Li+ ion diffusion inside the material and impedance spectroscopy shows enhanced lithium ion diffusion capabilities of the flakes. The proposed fabrication process is performed under ambient conditions and is simple, cost-efficient, fully scalable and can be easily transferred to other glass compositions with electrochemically active metal oxide
Keywords: Anode; Particle design; Glasses; Shape-anisotropy; Lithium-ion battery

SiO2–GeO2 Glass–Ceramic Flakes as an Anode Material for High-Performance Lithium-Ion Batteries - Esper, Julian Duane; Maußner, Felix; Romeis, Stefan; Zhuo, Ying; Barr, Maissa; Yokosawa, Tadahiro; Spiecker, Erdmann; Bachmann, Julien; Peukert, Wolfgang (Energy Technology, 2022)
The preparation of a flake-like glass–ceramic anode material comprised of SiO2 and GeO2 for Li-ion batteries (LIBs) is demonstrated. The precursor glass material is prepared via a traditional melt quenching technique. Flake-like glass particles are obtained by compression in the liquid phase via ball milling. A subsequent heat treatment induces crystallization of GexSiyO6 domains inside the vitreous SiO2–GeO2 matrix. This novel glass-ceramic material is applied as an anode material for LIBs and shows a stable reversible capacity of 520 mAh g−1 at 0.2 C combined with good capacity retention of 87% after 100 cycles. This cycling stability can be attributed to the synergistic effects of having nanocrystalline domains embedded in the glass matrix: The open glass network can withstand the volume change and stress caused by the lithium insertion during cycling, while the nanocrystals act as active sites for the electrochemical conversion and alloying reactions. The glass–ceramic anode material exhibits superior electrochemical properties compared to its pure glass counterparts.
CRIS-Team Scopus Importer:2022-06-10
Keywords: anodes; flake-like particles; glass ceramics; lithium-ion batteries; shape-anisotropy; thermal annealing